PENGARUH JUMLAH KUNJUNGAN WISATAWAN MANCANEGARA DAN JUMLAH HUNIAN HOTEL TERHADAP PENERIMAAN SUB SEKTOR PDRB INDUSTRI PARIWISATA DI PROVINSI SUMATERA UTARA TAHUN2004-2013 - Normaika Hutasoit; Harlen '; Azwar Harahap (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how much influence the number of tourist arrivals and hotel occupancy on the acceptance of the PDRB sectors of the tourism industry in the province of North Sumatra in 2004-2013. The data used is a time series data of the Central Bureau of Statistics and the Department of tourism. This study used quantitative research methods and using multiple linear regression analysis using SPSS 17 for windows. In this study, the independent variables are foreign tourists (X1) and hotel (X2) while the dependent variable is the PDRB (Y).Results of the research by using multiple regression analysis known and simultaneous regression test (Test F) note that Fhitung 392,891 dan Ftable 4.74 which is the confidence level of 5%. It is thus known that Fhitung> Ftabel (392.891> 4.74) showed that foreign tourists and hotels a significant effect on the PDRB in the province of North Sumatra. Partial regression test (t test) showed that the variables of foreign tourists and the hotel had a significant effect on the PDRB of North Sumatra Province. The magnitude of the effect that the (R 2) of 0.991.So, that’s to be mean of PDRB as the dependent variable is able to be explained by the independent variables namely foreign tourists and hotels amounted to 99.1% and the remaining 0.9% is explained by variables - other variables outside the research.Keyword: foreign tourists, Hotel, PDRB